Tahlîlu al-Adab al-Lughawî Ladã al-Dã’i bi Mãdûrã Wafqa li al-Dirãsah al-Baraghmãtiyyah wa al-Qurãn - Iswah Adriana; Waqiatul Masruroh (IAIN MADURA, 2019)
The study of politeness in the language is very important to do for a dai in terms of pragmatics and the Koran. The utterance in multicultural propaganda, as conveyed by the dai in Madura, shows the politeness of language as proclaimed by Pranowo in pragmatics and also according to the Qur'anic point of view. The research data were in the preacher form of speech from Madura during the lecture. The data source is several recorded lectures by KH. Musleh Adnan and Nyai Hj. Mufarrohah on YouTube. The data collection techniques were free listening, observation of speech and note-taking techniques. Data were analyzed by critical descriptive. The results revealed that: (1) The existence of politeness in the pragmatics of language that includes a sense of taste, adu rasa, empan papan, humble, respectful, tepa selira, and the use of diction